2022
DOI: 10.1002/ar.24903
|View full text |Cite
|
Sign up to set email alerts
|

Racism, structural racism, and the American Association for Anatomy: Initial report from a task force

Abstract: In 2021, the American Association for Anatomy (AAA) Board of Directors appointed a Task Force on Structural Racism to understand how the laws, rules, and practices in which the Association formed, developed and continues to exist affect membership and participation. This commentary is the first public report from the Task Force. We focus on African Americans with some comments on Jews and women, noting that all marginalized groups deserve study. Through much of its 130 year history, some members were an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Each country may have its own nefarious history of discriminatory anatomical body procurement, with Black 9 and Native American bodies procured in the US in the 19th century, and as such have need for more detailed studies of this history. 10 The tangible legacies from this history are found in anatomical and anthropological collections, which are now coming under increasing scrutiny. The intangible legacies from the history of racism are still obvious in the lack of diversity within anatomy faculty and anatomical images.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…Each country may have its own nefarious history of discriminatory anatomical body procurement, with Black 9 and Native American bodies procured in the US in the 19th century, and as such have need for more detailed studies of this history. 10 The tangible legacies from this history are found in anatomical and anthropological collections, which are now coming under increasing scrutiny. The intangible legacies from the history of racism are still obvious in the lack of diversity within anatomy faculty and anatomical images.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…The events that transpired during the Third Reich regarding macabre atrocities inflicted on human lives in the name of medical experiments and scientific studies are a lesson for any discipline (Pringle, 2010). Pursuing scientific knowledge and related experiments will be considered useful only if it follows moral principles and the outcome benefits humankind (Hildebrandt, 2022). The subsequent developments and deliberations after the fall of the Nazi regime emphasised the importance of defining limits in any scientific practice and respecting ethical boundaries.…”
Section: The G Ross D Is Reg Ard Of Informed Cons Ent During the Thir...mentioning
confidence: 99%
“…Accordingly, the task force's initial report was published in 2022, which observed that African Americans were underrepresented in the AAA compared to their US population. The recommendations of the task force were bi-pronged: (i) to acknowledge the finding and issue a statement accepting responsibility; (ii) to support positive measures which are already underway to improve the existing scenario (Sumner et al, 2022). The series involved a communication-based exercise between the faculty members and first-year medical students through a discussion on issues relevant to EDI.…”
Section: Increasing Awareness About Equality Diversity and Inclusivit...mentioning
confidence: 99%
“…The first section contains 11 manuscripts that address history and ethics in the anatomical sciences. Sumner et al ( 2022 ) report the initial findings of the AAA Task Force on Structural Racism, convened in the Spring of 2021 to examine how the structure of the organization contributes to the marginalization of some members. The task force found that throughout much of its history, the AAA has disregarded racism, and worse, admitted members who played essential roles in perpetuating racism.…”
Section: History and Ethics In The Anatomical Sciencesmentioning
confidence: 99%
“…I felt like the story of the Pernkopf atlas needed a platform for telling the entire membership, and so I proposed a detailed symposium with Dr. Jeff Laitman for the 2015 AAA meeting on Anatomy and the Holocaust, which was fitting as that year was the 70th anniversary of the liberation of Auschwitz on January 27, 1945. The symposium was not selected for programming (nor was it selected in 2016 when we proposed it again) because the AAA Professional Development Committee preferred to sponsor symposia that are “practical sessions that help members with issues related to their careers,” (Sumner et al, 2022 , appendix I). I was crushed.…”
Section: Introductionmentioning
confidence: 99%